A Low-cost Biomarker-based SAW-Biosensor Design for Early Detection of Prostate Cancer - ŞİŞMAN, ALPER; GÜR, ETKİ (ELSEVIER SCIENCE BV, 2017)
Early detection of prostate cancer is crucial for the treatment. Currently rectal examination, ultrasound and ELISA test for blood-PSA biomarker level are used for diagnosis. However these methods require professional assistance that makes point-of care (POC) testing impossible. A POC, low-cost, high-precision biosensor can increase the early-detection and survival rates. Recently, we have proposed a low-cost and an easy-to-use surface acoustic wave biosensor that enables the quantification of PSA level. In this study, we focused to the electronic circuitry and signal processing algorithms for accurate protein level assessment using cost efficient and low-profile hardware. Simplifying the hardware will potentially lead to the development of single chip monolithic integrated biosensor. The MEMS based biosensor designed in our studies utilizes shear-horizontal (SH) SAWs on ST-cut Quartz substrate to sense the mass loading change by protein adhesion. The driver circuitry employs signal-processing algorithms to detect the phase change, which quantifies the protein level in the sample dropped on the surface. The signal applied to the sensor input is a 16.9 MHz square wave generated by using a simple counter circuit. The output is under-sampled at an extremely low rate (100 KHz), then, the phase information is extracted using the under-sampled signal. A low-profile microcontroller (mu C) is used to determine the phase shift. The simulated and experimental results are demonstrated, and they agreed well with each other. The results show that, the phase error level is 1% and minimum delay measured is 0.3 ns. Increasing number of samples used for calculation enhances the detection performance. Our studies also showed that using excessive number of samples enables the accurate phase calculation even if a simple 1-bit ADC is employed. (C) 2017 The Authors. Published by Elsevier Ltd.
Keywords: Biosensor; Surface acoustic wave; acurate phase detection; MEMS